Kritik di Media Sosial dan Jerat Pidana Kasus Om Polos Banget dalam Perspektif Hukum Konsumen dan Hak Berkspresi - Kadek Ferdian Dwi Arsa (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Consumer criticism on social media is a common form of expression used to convey dissatisfaction with products or services. However, such criticism often generates controversy, especially when it is perceived to harm the reputation of a company. Although the right to freedom of expression is guaranteed by the Consumer Protection Law, in practice, this guarantee frequently conflicts with the defamation provisions outlined in the Electronic Information and Transactions (ITE) Law. The case of